2020
DOI: 10.1002/clc.23479
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cardiac function is associated with cardiac injury and mortality risk in hospitalized COVID‐19 Patients

Abstract: Background Cardiac injury is common in COVID‐19 patients and is associated with increased mortality. However, it remains unclear if reduced cardiac function is associated with cardiac injury, and additionally if mortality risk is increased among those with reduced cardiac function in COVID‐19 patients. Hypothesis The aim of this study was to assess cardiac function among COVID‐19 patients with and without biomarkers of cardiac injury and to determine the mortality risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Overall, the studies included a median of 52.0% (0.0–100.0) of patients admitted to ICU, undergoing forms of invasive or non-invasive mechanical ventilation in 57.0% (34.0–81.0) and 13.0% (8.6–32.7) of cases, respectively. Ten studies (32.2%) were retrospective [ 17 , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ], and 20 (66.6%) monocentric [ 15 , 17 , 18 , [20] , [21] , [22] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the studies included a median of 52.0% (0.0–100.0) of patients admitted to ICU, undergoing forms of invasive or non-invasive mechanical ventilation in 57.0% (34.0–81.0) and 13.0% (8.6–32.7) of cases, respectively. Ten studies (32.2%) were retrospective [ 17 , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ], and 20 (66.6%) monocentric [ 15 , 17 , 18 , [20] , [21] , [22] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ].…”
Section: Resultsmentioning
confidence: 99%
“… Authors Patients (n) Age (years) Male (%) B.M.I. Time to echo (days) HTN (%) DM (%) Obesity (%) CAD (%) Stroke (%) CKD (%) COPD (%) IMV (%) NIV (%) ICU (%) Garcia-Cruz et al [ 42 ] 82 56 (50–66) 62.2 0 (0) 47.6 43.9 79 21 100 Van den Heuvel et al [ 35 ] 51 63 (51–68) 80 27 (25–29) 41 18 10 4 2 12 33 37 Rath et al [ 32 ] 123 68 (15) 62.2 28 (5) 69.9 24.4 19.5 22.8 11.4 40 45.5 Chen et al [ 25 ] 143 67 (16) 62 29 (6.3) 69 38 30 10 19 35 Schott et al [ 45 ] 66 60 (16) 57.6 43 (12) 3 (4,5) 57.6 34.8 15.2 4.5 12.1 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, numerous epidemiological studies have shown an increased risk of AF and new-onset AF among patients with COVID-19 but have yielded inconsistent results (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Moreover, accumulating literature has demonstrated that AF or new-onset AF might be significantly associated with the worst outcomes (e.g., mortality) in patients with COVID-19 (21,25,29).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent study revealed that cavin-1 deficiency affects a number of coronary and myocardial functions, including ischaemic tolerance and stretch responses [ 99 ]. Interestingly, cardiac injury has been reported in COVID-19 patients [ 100 ], even in the absence of coronary arteries obstruction [ 101 ], therefore unlikely to be caused by altered coagulation observed in these patients [ 102 ]. Furthermore, a mechanism of entry of SARS-CoV-2 in cardiomyocytes has been recently proposed [ 103 ].…”
Section: Discussionmentioning
confidence: 99%